2022
DOI: 10.3390/ijerph19148574
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Migrant Farmworkers’ Health and Well-Being during the Global COVID-19 Pandemic in Canada: Toward a Transnational Conceptualization of Employment Strain

Abstract: During the COVID-19 pandemic, Canada imposed certain international travel bans and work-from-home orders, yet migrant farmworkers, declared essential to national food security, were exempt from such measures. In this context, farm worksites proved to be particularly prone to COVID-19 outbreaks. To apprehend this trend, we engaged an expanded and transnational employment strain framework that identified the employment demands and resources understood from a transnational perspective, as well as the immigration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although health is one of the most important determinants of well-being, agricultural workers make insufficient use of health services in most regions of the world [ 19 ]. In a study conducted in Canada, it was determined that migrant agricultural workers could not be adequately protected during the pandemic period, and a low level of welfare was found in the workers in this process [ 20 ]. In our study, it was found that employees were not sufficiently protected from covid 19 and had low welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Although health is one of the most important determinants of well-being, agricultural workers make insufficient use of health services in most regions of the world [ 19 ]. In a study conducted in Canada, it was determined that migrant agricultural workers could not be adequately protected during the pandemic period, and a low level of welfare was found in the workers in this process [ 20 ]. In our study, it was found that employees were not sufficiently protected from covid 19 and had low welfare.…”
Section: Discussionmentioning
confidence: 99%
“…These issues became particularly salient during the Coronavirus Disease-2019 (COVID-19 pandemic) which involved social distancing measures to be put in place and prohibited many in-person interactions like conducting in-person interviews, focus groups, and surveys. While there have been few cross-sectional reports indicating migrant farmworkers faced heightened vulnerabilities during the COVID-19 pandemic [ 11 , 12 ], to date, there has been no published longitudinal study of the mental health of migrant farmworkers in the U.S. during the pandemic. Even beyond the pandemic, there is great utility in understanding the best methods to survey this important vulnerable working population.…”
Section: Introductionmentioning
confidence: 99%
“…The authors use study designs and logics derived from epidemiology, community-based (participatory) research, and the social sciences, employing qualitative, quantitative, and mixed-methods approaches to gather their data and undertake their analyses. As we considered the research, we categorized it into three general but not mutually exclusive content groupings, as follows: Studies that highlight the ways in which work interacts with other social phenomena to influence health [ 1 , 2 , 3 , 4 , 5 ]; Studies that focus on the context in which work happens and emphasize the importance of that context in shaping work or health [ 6 , 7 , 8 , 9 ]; Studies that encourage us to think more expansively about work [ 10 , 11 ]. …”
mentioning
confidence: 99%
“…Studies that focus on the context in which work happens and emphasize the importance of that context in shaping work or health [ 6 , 7 , 8 , 9 ];…”
mentioning
confidence: 99%
See 1 more Smart Citation